PELAKSANAAN PRAKTIK KERJA INDUSTRI PADA PESERTA DIDIK KELAS XI DI SMK NEGERI 2 KARANGANYAR DENGAN MODEL KIRKPATRICK - Ayu Nuvita Sari; Muhammad Akhyar; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
This study aims at: (1) obtaining a description the quality of implementation Internship Program Competency Ototronic Engineering class XI in SMK Negeri 2 Karanganyar in terms of the Reaction component; (2 obtaining a description the quality of implementation Internship Program Competency Ototronic Engineering class XI in SMK Negeri 2 Karanganyar in terms of the Learning component; (3) obtaining a description the quality of implementation Internship Program Competency Ototronic Engineering class XI in SMK Negeri 2 Karanganyar in terms of the Behavior component.This research was conducted at SMK Negeri 2 Karanganyar. This study was included in the type of evaluative research (evaluation research) where the evaluation model used was Kirkpatrick's evaluation model. The population in the study were students of SMK Negeri 2 Karanganyar at the Ototronic Engineering Expertise Program and the supervisor of the school in the ototronic engineering expertise program and supervisors in the industry who directly assisted the implementation of industrial work practices. The number of respondents was 108 students, 5 mentors for the ototronic engineering expertise program, and 5 mentors in the industry. Data collection techniques in this study used a questionnaire method that was distributed to students, an interview method with some student respondents, and all school supervisors and industry teachers, and documentation of the final score of Internship. Validity uses fact finding, namely the validity of logic. Therefore, fact finding for reliability testing is not necessary. Score analysis uses average analysis which will be assessed based on research criteria. The results of the study show: (1) aspects of reaction with student respondents who have an average value of 3.88 which includes very high criteria, this is indicated by the results on the indicators giving direction of 3.99; (2) aspects of evaluating learning with student respondents who have an average value of 3.82 which includes very high criteria, this is intended with the results on the discipline indicator of 4.00; (3) aspects of behavior evaluation with student respondents who have an average value of 4.07 which includes very high criteria, this is indicated by the results on the skills indicator after the internship is 4.25; (4) from the results of research conducted to obtaining a comprehensive picture when viewed from the components of reaction, learning, and behavior is very high including very high criteria.